Program Pengembangan Keterampilan Resiliensi untuk Meningkatkan Self-esteem pada Remaja - Fi Aunillah; Maria Goretti Adiyanti (Faculty of Psychology, Universitas Gadjah Mada, 2015)
Social discrepancy can occurs in some favourite junior high schools. Based on the preliminary study in 2013, it caused the students with low socio-economic status to have a negative view of themselves and the environment, feel depresed, feel unconfident, and inhibit the self optimization. One of the factors that support the self growth and resiliency in adolescent is the self esteem that can be developed by resilience skills development program. This study was aimed to examine the effectiveness of the program in enhancing the self-esteem among adolescent with low socio economic status. It used quasi-experimental design. The subjects were the students of SMPN X and Y in Yogyakarta, that are labelled as favourite junior high schools. The data was analized using Mann-Whitney U Test to test the program effectiveness. The result shows that the program can enhance the self esteem significantly among adolescent with low socio-economic status.